2015
DOI: 10.1016/j.enpol.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Gone with the wind? The impact of wind turbines on tourism demand

Abstract: While wind energy production is relatively free from environmental externalities such as air pollution, it is frequently considered to negatively impact landscapes' visual aesthetic values, thereby inducing negative effects on tourism demand. Existing evidence for Germany indeed points towards a negative relationship between tourism demand and wind turbine construction. However, the existing studies primarily rely on interview data and simple bivariate statistics. In contrast, we make use of secondary statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 26 publications
0
31
0
4
Order By: Relevance
“…Research on this topic shows conflicting results: some studies show that wind farms may have a negative effect on tourism demand and tourism expenditures in the affected area (Broekel and Alfken, 2015;Riddington et al, 2010), whereas others demonstrate that they are innocuous in terms of local tourism demand, expenditures and experiences (Aitchison, 2012;Frantál and Kunc, 2011;Sousa and Kastenholz, 2015;Warren and McFadyen, 2010), and can even function as tourist attractions per se in some rural areas (Aitchison, 2012;Frantál and Kunc, 2011;Pasqualetti, 2004).…”
Section: State Of the Artmentioning
confidence: 99%
“…Research on this topic shows conflicting results: some studies show that wind farms may have a negative effect on tourism demand and tourism expenditures in the affected area (Broekel and Alfken, 2015;Riddington et al, 2010), whereas others demonstrate that they are innocuous in terms of local tourism demand, expenditures and experiences (Aitchison, 2012;Frantál and Kunc, 2011;Sousa and Kastenholz, 2015;Warren and McFadyen, 2010), and can even function as tourist attractions per se in some rural areas (Aitchison, 2012;Frantál and Kunc, 2011;Pasqualetti, 2004).…”
Section: State Of the Artmentioning
confidence: 99%
“…Broekel et al . studied the relation between the tourism industry and the wind turbines' construction, which may not be obvious, but the results show that constructing the wind turbines has negative impact on the amount of tourism traveling to that region, a Germany case study. By analyzing the life cycle emissions related to the production of wind power, they concluded that emissions are fairly small .The GHG emissions vary between 4 and 68 g CO 2 g/kWh, NOx emissions between 0.01 and 0.02 g/kWh, and SO 2 emissions between 0.036 and 0.04 g/kWh.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from direct negative effects on human ecology (Scherhaufer et al 2017) people might simply be annoyed by a wind farm that spoils the landscape character, causes visual intrusions (D'Souza and Yiridoe 2014), reduces the quality of the recreational area (Broekel and Alfken 2015;Frantál and Kunc 2011) and on top of that generates unpleasant noise. Rand and Hoen (2017) found in their review that sound and visual impacts strongly tie to annoyance and in further consequence opposition.…”
Section: Theoretical Background: Public Acceptance Of Wind Powermentioning
confidence: 99%
“…Energy tourism as a new niche of industrial tourism might even be a strategic tool to rebrand the image and to strengthen the competitive potential of the region (Frantál and Urbánková 2017). However, high acceptance should not be taken for granted, especially with an increasing number and size of wind turbines on the mountain ridges that are clearly visible even from a very great distance (Broekel and Alfken 2015). Moreover, one needs to be aware of the fact that the construction of wind power plants in the mountains always requires access to the construction site with large trucks in order to transport the turbines and other components.…”
Section: Policy Implicationsmentioning
confidence: 99%